Geochemical and mineralogical aspects of the Molteno Formation, South Africa - Reynolds, Adrian J (Rhodes University, Faculty of Science, Department of Geology, 1980)
The Triassic Molteno Formation is a clastic sedimentary sequence consisting of a series of cycles, dominated lithologically by coarse grained sandstones. Aspects of the petrography have been examined using the conventional petrographic microscope as well as the scanning electron microscope. Both solution and overgrowth features are present not only on the quartz grains but also on certain of the heavy mineral species present. Intrastratal solution of garnet would appear to be a significant feature in the Molteno Formation. Mineralogical examination of the laterally persistent Indwe Sandstone Member indicates no significant variation in heavy mineral content. Evidence from a study of zircon elongation ratios shows the presence of two distinct zircon populations indicating two provenance areas. X-ray diffraction and electron microprobe analysis has identified mineral species characteristic of granites, pegmatitic granite and metamorphic rocks, especially amphibolites. Palaeocurrent data indicates that this source area lay to the south-east; to the south the source area consisted mainly of the Cape Supergroup sediments. Analysis for Nb, Zr, Y, Sr, Rb, Zn, Mn, Ba, Cu, Ni, Co, Cr, V and Ti for 22 samples from the Molteno Formation, indicates, as expected for a highly arenaceous sequence, a substantial depletion in these trace elements. No consistent variation of trace element concentration occurs with height in the sequence so trace element content may not be used for purposes of stratigraphic correlation. There are indications of trace element variation with geographical position, no doubt a reflection of the contribution of 2 source areas of different compositions. Factor analysis of the interelement correlations has identified 3 factors which influence the trace element content of the Molteno Formation these are a "heavy mineral" factor, a "pH-Eh" factor and a "clay mineral" factor. These trace factors are ultimately an expression of the source rock composition, the prevailing climate and a combination of the two. Comparison with the more argillaceous overlying Elliot Formation, indicates that factors influencing geochemical variation in this sequence were far more complex than for the Molteno Formation
Keywords: Sediments (Geology) -- South Africa; Mineralogy -- South Africa; Petrology -- South Africa; Geochemistry -- South Africa; Molteno Formation (South Africa)